Role of UHRF1 in de novo DNA methylation in oocytes and maintenance methylation in preimplantation embryos - Maenohara, Shoji (PLoS Genet, 2017)
The methylation of cytosine at CG sites in the mammalian genome is dynamically reprogrammed during gametogenesis and preimplantation development. It was previously shown that oocyte-derived DNMT1 (a maintenance methyltransferase) is essential for maintaining and propagating CG methylation at imprinting control regions in preimplantation embryos. In mammalian somatic cells, hemimethylated-CG-binding protein UHRF1 plays a critical role in maintaining CG methylation by recruiting DNMT1 to hemimethylated CG sites. However, the role of UHRF1 in oogenesis and preimplantation development is unknown. In the present study, we show that UHRF1 is mainly, but not exclusively, localized in the cytoplasm of oocytes and preimplantation embryos. However, smaller amounts of UHRF1 existed in the nucleus, consistent with the expected role in DNA methylation. We then generated oocyte-specific Uhrf1 knockout (KO) mice and found that, although oogenesis was itself unaffected, a large proportion of the embryos derived from the KO oocytes died before reaching the blastocyst stage (a maternal effect). Whole genome bisulfite sequencing revealed that blastocysts derived from KO oocytes have a greatly reduced level of CG methylation, suggesting that maternal UHRF1 is essential for maintaining CG methylation, particularly at the imprinting control regions, in preimplantation embryos. Surprisingly, UHRF1 was also found to contribute to de novo CG and non-CG methylation during oocyte growth: in Uhrf1 KO oocytes, transcriptionally-inactive regions gained less methylation, while actively transcribed regions, including the imprinting control regions, were unaffected or only slightly affected. We also found that de novo methylation was defective during the late stage of oocyte growth. To the best of our knowledge, this is the first study to demonstrate the role of UHRF1 in de novo DNA methylation in vivo. Our study reveals multiple functions of UHRF1 during the global epigenetic reprogramming of oocytes and early embryos.